Penerapan E-Module Interaktif untuk Meningkatkan Motivasi dan Hasil Belajar IPA Peserta Didik Kelas VII SMP Negeri 27 Makassar - Nur Afni Yunita Idris; Salma Samputri; Nurhayani H. Muhiddin (Celebes Science Education, 2026)
This research aims to find out: 1) The level of motivation and learning outcomes of students in class VII SMPN 27 Makassar before the application of interactive e-module on the material of living things composed of cells. 2) The level of motivation and learning outcomes of students of class VII after the application of interactive e-module 3) The increase in motivation and learning outcomes of students grade VII after the application of interactive e-module 4) Significant increase in motivation and learning outcomes of students of class VII after the application of interactive e-module. The type of research was Pre-Experimental design. The analysis concluded that: 1) The level of motivation and learning outcomes of science students in class VII SMPN 27 Makassar before the application of interactive e-module with a pretest score of 73.19 motivation is in the high category and the pretest score of learning outcomes 5,92 is in the medium category. 2) The level of motivation and learning outcomes of science students in class VII after the application of interactive e-module with a motivation posttest score of 85.73 in the very high category and a learning outcome posttest score of 9,50 in the high category. 3) The level of motivation and science learning outcomes of VII grade students after the application of interactive e-module with N-Gain motivation 0.47 is in the medium category and N-Gain learning outcomes 0.56 is in the medium category. 4) There is a significant increase in motivation and learning outcomes of science students in class VII SMPN 27 Makassar after the application of interactive e-module.